Sistem Pakar Diagnosa Penyakit Panleukopenia Pada Kucing Menggunakan Metode Naïve Bayes - Sadikin, Arif Maulana; Witanti, Arita (Universitas Multi Data Palembang, 2025)
This study aims to design and develop an expert system that can assist in diagnosing panleukopenia in cats using the Naïve Bayes method. Panleukopenia is a contagious disease with a high mortality rate, making early detection crucial to increasing the chances of recovery. The Naïve Bayes method was chosen for its ability to process probability-based data and provide accurate predictions based on the given symptoms. The system was developed based on information from veterinary medical experts and relevant scientific references. To ensure the system’s quality, validation was conducted by comparing the system’s diagnostic results with those provided by veterinarians. Testing results showed that the system achieved an accuracy rate of 93,3%, indicating that this method is effective in supporting the early diagnosis of panleukopenia. Therefore, the system is expected to serve as a useful tool for pet owners and medical profesionals in making further treatment decisions.